Robenacoxib shows efficacy for the treatment of chronic degenerative joint disease-associated pain in cats: a randomized and blinded pilot clinical trial - Derek Adrian (Nature Portfolio, 2021)
Abstract The main objective of this pilot clinical trial was to evaluate outcome measures for the assessment of the nonsteroidal anti-inflammatory drug (NSAID) robenacoxib in cats with degenerative joint disease-associated pain (DJD-pain). Otherwise healthy cats (n = 109) with DJD-pain entered a parallel group, randomized, blinded clinical trial. Cats received placebo (P) or robenacoxib (R) for two consecutive 3-week periods. Treatment groups were PP, RR, and RP. Actimetry and owner-assessment data were collected. Data were analyzed using mixed-effects and generalized mixed-effects linear models. Activity data showed high within-cat and between-cat variability, and 82.4% of the values were zero. Compared to placebo, mean total activity was higher (5.7%) in robenacoxib-treated cats (p = 0.24); for the 80th percentile of activity, more robenacoxib-treated cats had a > 10% increase in activity after 3 (p = 0.046) and 6 weeks (p = 0.026). Robenacoxib treatment significantly decreased owner-assessed disability, (p = 0.01; 49% reduction in disability; effect size ~ 0.3), and improved temperament (p = 0.0039) and happiness (p = 0.021) after 6 weeks. More robenacoxib-treated cats were successes at 6 weeks (p = 0.018; NNT: 3.8). Adverse effect frequencies were similar across groups. Results identified suitable endpoints for confirmatory studies, while also indicating efficacy of robenacoxib in cats with DJD-pain.